The colonization of maize seedling roots and rhizosphere by Fusarium spp. in Mississippi in two soil types under conventional tillage and notillage systems - Soonthornpoct, P.; Trevathan, L.E.; Ingram, D. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 2000)
Pioneer 3167 hybrid maize was planted on two soil types in Mississippi on four dates annually from 1995 to 1997 and was sampled at weekly intervals beginning one week and ending 4 weeks after planting. Plots were either tilled with a do-all and rows formed in the fall or were left undisturbed until planting in the spring. Under tillage, Fusarium spp. were isolated most frequently at the earliest and latest planting dates when seedlings were sampled at 10 and 17 days. In no-tillage plots, the overall isolation frequency was lower than in conventional-tillage plots and decreased with later planting dates and sampling times. The highest Fusarium populations were found in the rhizosphere of a silt loam in conventional-tillage plots when seedlings were sampled 28 days after the second planting in 1997, compared to populations from a silty clay soil. Fusarium moniliforme, F. solani and F. oxysporum were the predominant Fusarium spp. isolated from maize seedling roots. In pathogenicity tests, F. moniliforme and F. solani produced measurable effects on maize seedlings. F. moniliforme reduced the length of primary roots and decreased the number of secondary roots, and F. solani reduced root dry weight of maize seedlings.